An exploratory study of the tax rate reconciliation disclosures of JSE listed companies - Rudie Nel; Anja van Niekerk (South African Journal of Economic and Management Sciences)
Background: Tax rate reconciliations provide stakeholders (investors, analysts and regulatory bodies) with an understanding of the relationship between accounting profits and tax expenses as well as assist researchers in understanding the sources of variation in effective tax rates.